Taguchi-based optimisation of FSW parameters for advancement in aerospace materials: Al-Li 2060 alloy - Noah E. El-Zathry; Stephen Akinlabi; Wai Lok Woo; Vivek Patel; Rasheedat M. Mahamood (Heliyon)
Aluminium-lithium (Al-Li) 2060 alloy, a 3rd generation Al-Li alloy, is considered a structural material for aircraft components. This study employs the Friction Stir Welding (FSW) process with a kinematic 5-axis robotic arm to weld 4-mm-thick plates of 2060-T8E30 Al-Li alloy. The focus is on the impact of tool axial force and speeds on the microstructural evolution, mechanical properties, and surface integrity of the welded joints. The applied process parameters included rotational speeds ranging from 800 to 1600 rpm, traverse speeds from 2 to 4 mm/s, and axial forces from 4 to 6 kN. We utilise the Taguchi L9 orthogonal array to optimise the process parameters. The results revealed that rotational speed is paramount for affecting the welds' quality, followed by axial force and then traverse. Defect-free samples exhibited a fine surface finish, with average roughness values of 3.05 μm and 3.536 μm. The study also showed that 5 kN of axial force, 1200 rpm of rotational speed, and 3 mm/s of traverse speed were the best FSW conditions for getting a maximum stir zone microhardness value of 128.77 HV. This study also shows how to improve the FSW parameters for Al-Li alloys, showing how important precise parameter control is for improving joint strength and weld quality in high-tech aerospace and automotive applications.